Practical guidelines for standardising the measurement of resting metabolism by indirect calorimetry: a literature review - A. G. Antonov; V. D. Vybornov; M. Y. Balandin; P. D. Rybakova; V. A. Badtieva; D. B. Nikityuk; Ye. A. Rozhkova (National Electronic Information Consortium (NEICON), 2022)
Accurate resting metabolic rate readings are essential for dietary planning and body composition monitoring not only for healthy individuals but also for athletes. A number of factors can alter resting metabolic rate during its measurement by indirect calorimetry. The methodology used may affect the results of the study. A clear standardisation of this procedure is needed to obtain the most accurate results.Purpose: To review the literature to determine the optimal subject condition and methodology for the resting metabolism measurement procedure using indirect calorimetry.Materials and methods: A literature search was conducted in PubMed, MEDLINE and Cochrane Library databases. The query included key words and logical phrases: "calorimetry", "indirect calorimetry", "resting metabolic rate", "energy metabolism", "basal metabolism", "standards". Only English-language studies and human studies were considered. Additional information was identified because of the review and included in the review.Results: the parameters of standardization during the resting metabolism measurement procedure are described: consumption of food, ethanol, caffeine, nicotine; daily activities and physical activity; body position in space and environmental conditions during the measurement; actions of the specialist performing the procedure, etc. The article outlines effective methods for measuring resting metabolism to obtain the most accurate results in both healthy individuals and athletes.Conclusion: an attempt has been made to formulate precise methodological rules for standardisation and recommendations for measuring resting metabolism by indirect calorimetry.